2022
DOI: 10.1177/10870547221085502
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Bullying Victimization and Bullying Perpetration in Children and Adolescents With ADHD: 2016 to 2017 National Survey of Children’s Health

Abstract: Objective: To identify characteristics associated with bullying involvement in pediatric ADHD. Methods: Data from the 2016 to 2017 National Survey of Children’s Health for children aged 6 to 17 years with ADHD were evaluated to assess the association between parent-reported bullying victimization or perpetration and the following potential predictors: demographic characteristics, family factors, school factors, and child conditions/behaviors. Results: Among children with ADHD, 46.9% were bullying victims and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Previous research shows a positive association between ADHD and bullying involvement. Cuba Bustinza et al 21 reported a higher prevalence of victimisation in children diagnosed with ADHD. This study showed no statistically significant difference between bullies and victims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research shows a positive association between ADHD and bullying involvement. Cuba Bustinza et al 21 reported a higher prevalence of victimisation in children diagnosed with ADHD. This study showed no statistically significant difference between bullies and victims.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mental health predisposed to being the victim of bullying, illustrating ‘bi-directionality of relationships between bullying victimisation and mental health outcomes’ (p. 1313). 4 For example, Cuba Bustinza et al 21 reported on the characteristics of children diagnosed with attention-deficit/hyperactivity disorder (ADHD) using data from a national survey. Almost half of the children diagnosed with ADHD were victims (46.9%), compared with 16.2% who were perpetrators.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ADHD in children with epilepsy is five to ten times higher than that in controls without epilepsy (Cohen et al., 2013 ; Wagner et al., 2021 ). A study of 91,605 children (<17 years of age) from the National Survey of Children's Health in America, including 977 children with epilepsy, found that the prevalence of ADHD was much higher than that in children without epilepsy (23% vs. 6%) (Adams & Claussen, 2022 ). Conversely, epilepsy occurs approximately 4 times more frequently in children with ADHD than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Mediating and moderating factors associated with bullying perpetration are parental anger, poverty, poor relationships with parents, lack of school engagement, and peer conflicts. 8 , 17 More research is also needed about the effects of bullying victimization and perpetration such as (1) whether there are more severe outcomes for youth who are bullied by the opposite versus same sex, (2) whether mental distress is more severe among youth who experience intra-racial/ethnic bullying based on racial identity (e.g., contested racial authenticity) as opposed to inter-racial/ethnic bullying, and (3) in terms of bullying based on race/ethnicity and other identities, the experience of same-group bullying or “othering.”…”
Section: New Areas For Research On Bullyingmentioning
confidence: 99%